2018
DOI: 10.17814/mechanik.2018.4.46
|View full text |Cite
|
Sign up to set email alerts
|

Flexible PC-based CNC machine control system

Abstract: In the article a PC-based CNC machine control system is presented which communicates with servo drives and auxiliary input/output devices via EtherCAT bus. LinuxRTAI real-time operating system and LinuxCNC control software were implemented in the PC controller. A software module implementing EtherCAT communication with the servo drives was developed and integrated with LinuxCNC. Experimental results were presented which show the trajectory smoothing capabilities of the control system. Experimental results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…4 Paprocki M's team analyzed the low efficiency of current CNC systems and proposed a new control system for CNC machines, which communicates with auxiliary devices and servo drives via a bus, enabling fast two-way communication between the controller and servo drives, which was shown to be can be applied to different configurations of machines. 5 Lü et al developed an integrated control strategy integrating a zero-phase tracker controller and a modal filter controller to cope with the tracking errors and low machining accuracy that occur in high-speed operation of CNC machine tools, using the principle of zero-pole pair elimination and by setting the inverse function of the transfer function of the system. The results showed that it improved the phase lag of the servo feed system, reduced errors and improved efficiency.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Paprocki M's team analyzed the low efficiency of current CNC systems and proposed a new control system for CNC machines, which communicates with auxiliary devices and servo drives via a bus, enabling fast two-way communication between the controller and servo drives, which was shown to be can be applied to different configurations of machines. 5 Lü et al developed an integrated control strategy integrating a zero-phase tracker controller and a modal filter controller to cope with the tracking errors and low machining accuracy that occur in high-speed operation of CNC machine tools, using the principle of zero-pole pair elimination and by setting the inverse function of the transfer function of the system. The results showed that it improved the phase lag of the servo feed system, reduced errors and improved efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…The differential, integral and proportional gains of the PID controller correspond to the connection weights of the neural network. The PID structure can be simulated by expressing the output function of the neuron as a linear function, the equation of which is given in Equation (5).…”
Section: Single Neuron Pid Algorithm Based On Fuzzy Controlmentioning
confidence: 99%
See 1 more Smart Citation